1999
DOI: 10.1111/j.1365-2141.1999.01294.x
|View full text |Cite
|
Sign up to set email alerts
|

Spleen stromal cells support haemopoiesis and in vitro growth of dendritic cells from bone marrow

Abstract: Summary. Long-term stroma-dependent cultures from murine spleen have been previously shown to support dendritic cell (DC) development in vitro. Secondary cultures have now been established using a splenic stromal cell layer overlaid with cells from different lymphoid sites. Cells resembling DCs can be generated in vitro from unfractionated murine lymphoid cells in the absence of added growth factors. Bone marrow (BM) cultures are the most successful but some cultures have been derived from spleen and thymus. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 35 publications
0
32
1
Order By: Relevance
“…Previously it was shown that cells resembling DC both functionally and phenotypically could be produced in LTC without the addition of an exogenous source of GM-CSF ,1999). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously it was shown that cells resembling DC both functionally and phenotypically could be produced in LTC without the addition of an exogenous source of GM-CSF ,1999). …”
Section: Discussionmentioning
confidence: 99%
“…Another consideration is whether LTC-DC are more closely related to the apparent myeloid or lymphoid DC lineages (Shortman & Caux, 1997 (BM) as previously described (Ni & O'Neill, 1997;1999 In vitro agar colony assay…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Established LTC do not produce lymphoid cells, granulocytes, or monocytes͞macrophages (11)(12)(13). Production of cells expressing markers associated with DC, including CD11c, CD11b, DEC-205, and 33D1, has been shown to continue for up to 7 years for some LTC (14).…”
mentioning
confidence: 99%
“…A long-term culture (LTC) system that supports hemopoiesis has been developed from murine spleen that continuously produces nonadherent DC (LTC-DC), in the absence of exogenous growth factors, including granulocyte͞ macrophage colony-stimulating factor (11)(12)(13). The production of LTC-DC appears to depend on the maintenance of small progenitor cells carried through many passages of cultures.…”
mentioning
confidence: 99%